Lei de cotas na Universidade Federal do Ceará (UFC): avaliação dos seus impactos - Araújo, Adriana Castro (2021)
The quota system currently in use within the Federal Higher Education Institutions (IFES), supported by Law No. 12,711 / 2012, represents an emergency measure whose objective is to diminish the reflexes of the country's social heterogeneity. In order to appraise the impacts of this action within the scope of the Federal University of Ceará (UFC – Universidade Federal do Ceará in Portuguese), an ex-post facto type of research was carried out in order to test four hypotheses: a) Hypothesis A: the average score of the freshmen before the implementation of the Quota Law is significantly higher than the average score of new entrants after the implementation of the Quota Law; b) Hypothesis B: the average Academic Performance Index (IRA – Índice de Rendimento Acadêmico in Portuguese) of students before the implementation of the Quota Law is not significantly different from the average IRA of students after the implementation of the Quota Law; c) Hypothesis C: the average dropout rate of students before the implementation of the Quota Law is significantly higher than the average dropout rate of students after the implementation of the Quota Law; d) Hypothesis D: the Graduation Success Rate (TSG – Taxa de Sucesso da Graduação in Portuguese) before the implementation of the Quota Law is significantly lower than the TSG after the implementation of the Quota Law. To support this research, the evaluation models that were related to the central theme of the study were presented, as well as the definition and methodology aimed at impact assessment. To this end, authors such as Ralph Tyler, Stufflebeam, Scriven, Shinkfild, Andriola, Baker, Ferraro, Morh, Leeuw and Vaessen, Cohen and Franco, Amaral, Contreras, Chianca, among others, were cited. The hypotheses were tested using the Interrupted Time Series method, considering the period before and after the implementation of the Quota Law. In the period after the quotas, the non-equivalent control group method was used in order to compare the performance between quota students and non-quota students. It was found that the first hypothesis was corroborated, since the average score of UFC entrants decreased significantly after the implementation of the Quota Law. In addition, when comparing the average ticket score between quota holders and non-quota holders, it was found that the difference found can be attributed to the Quota Law, since those had lower entry scores. The second hypothesis was also corroborated, as it was found that there was no significant difference between the average IRA of incoming students before and after the implementation of the Quota Law. The third hypothesis was refuted, as we did not identify any difference in the average dropout rate when comparing the scenario before and after the Quota Law. However, in the scenario after the Quota Law, quota students showed an evasion rate significantly higher than non-quota students. The fourth and last hypothesis has also been refuted. It was found that the TSG of the period after the UFC Quota Law was significantly lower when compared to the period prior to the implementation of that law. It was also found that the TSG of quota students was significantly lower than the TSG of non-quota students, which allowed us to conclude that the quotas had a negative impact on this indicator. Therefore, high dropout rates and low TSG were identified among quota students. Thus, it is important to investigate how the UFC's undergraduate courses are being managed, as well as the adaptation process of these students, above all, because the university environment in which the student is inserted may be one of the main factors associated with academic failure.